Lessons and legacies XIV : the Holocaust in the twenty-first century : relevance and challenges in the digital age - Lessons and Legacies Conference on the Holocaust; Cole, Tim 1970- HerausgeberIn VerfasserIn einer Einleitung; Gigliotti, Simone 1973- HerausgeberIn VerfasserIn einer Einleitung (Northwestern University Press, 2021)
Introduction: The Holocaust in the Twenty-First Century / Tim Cole and Simone Gigliotti -- Reimagining the "Gray Zone": Female Prisoner Functionaries in the Gross-Rosen Subcamps, 1944-45 / Andrea Rudorff -- The Muselmann Liberated: Impossible Holocaust Metaphors in Survivor Memoirs and Photography / Sharon B. Oster -- Absent Presence, Pathological Afterimages, and the Aesthetics of Excrement / Holli Levitsky -- When One Door Closes, Another Opens: The Demjanjuk Trials in Israel (1986-1993) and in Germany (2009-2011) / Yehudit Dori Deston -- The Geographies of Living Underground: Escape Routes and Hiding Spaces of Fugitive Jews in Germany, 1939-1945 / Susanna Schrafstetter -- Bella Hazan Ya`ari: A Member of the Jewish Resistance in Pursuit of Self and a Future / Dalia Ofer -- Migration Narratives of Holocaust Survivors in Chile, Colombia, and Mexico / -- Lorena Avila, Nancy Nicholls, and Yael Siman -- A Different Approach to Microhistory: The Arrests of the Jews of the Vaucluse as Seen through Quantitative Prosopography / Adrien Dallaire -- Mind the Gap: Reading across the Holocaust Testimonial Archive / Anne Kelly Knowles, Paul B. Jaskot, Tim Cole, and Alberto Giordano -- When the Index Is Wrong: Exploring Black Holes in Victim Memory / Hannah Pollin-Galay -- People, Places, Things: Considering the Role of Visitor Photography at the United States Holocaust Memorial Museum / Meghan Lundrigan